Astronomia indígena no ensino de sistemas de referência a partir da teoria da atividade histórico-cultural - Freitas, Nairys Costa de; Moreira, Heliomárzio Rodrigues; Romeu, Mairton Cavalcante; Barroso, Maria Cleide da Silva (Góndola, enseñanza y aprendizaje de las ciencias, 2026)
This paper is a theoretical essay whose objective is to propose the integration of Indigenous Astronomy into the teaching of Reference Systems considering the Theory of Historical-Cultural Activity (THCA). It seeks to answer the following research question: how can the astronomical knowledge of Indigenous peoples be integrated into the teaching of Reference Systems without falling into epistemological reductionism? Through a critical analysis that examines the connections and limitations between the materialist foundations of HCT, symbolic structures, and indigenous ontologies, the study reflects on the complexity of fostering intercultural dialogue in science education. Based on an analysis of curriculum documents and theoretical foundations, the study proposes pedagogical approaches aimed at developing teaching materials that value ethnic-racial relations and environmental education. Using Reference Systems and indigenous celestial knowledge as integrating axes, the essay problematizes cultural incommensurability and advocates for epistemic justice against historical silencing in science curricula. Supported by Law No. 11,645/2008 and the BNCC, the approach expands the principles of cultural mediation toward an emancipatory praxis, asserting that the voices and participation of Indigenous peoples should assume a permanent and ethical centrality in educational spaces.